2021
DOI: 10.1155/2021/6473038
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miR-23b in Cancer and Autoimmune Disease

Abstract: Short-stranded miRNAs are single-stranded RNA molecules involved in the regulation of gene expression. miRNAs are involved in a variety of cellular physiological processes, including cell proliferation, differentiation, and apoptosis. miR-23b have been identified to act both as oncogenes and as tumor suppressors. In addition, miR-23b is related to inflammation resistance to various autoimmune diseases and restrained inflammatory cell migration. The characterization of the specific alterations in the patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…MiR-23b plays contrary roles in different types of cancer but is a tumor suppressor miRNA in EC 29 , 30 . MiR-23b targets metastasis-associated in colon cancer-1 (MACC1) inhibiting EC cells proliferation, invasion, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-23b plays contrary roles in different types of cancer but is a tumor suppressor miRNA in EC 29 , 30 . MiR-23b targets metastasis-associated in colon cancer-1 (MACC1) inhibiting EC cells proliferation, invasion, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…miR-23b is a member of the miR-23-27-24 family which consists of two paralogs with the miR-23a cluster (miR-23a-27a-24-2) found on chromosome 19 and the intragenic miR-23b cluster (miR-23b27b-24-1) located on chromosome 9 within the C9orf3 gene [ 24 ]. Previous research suggested that miR-23b plays vital roles in cancer development where it exerts either oncogenic or tumor suppressor activity [ 25 , 26 ]. It is also implicated in the regulation of angiogenesis and endothelial cells homeostasis and may serve as biomarkers for the early diagnosis of acute myocardial infarction [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results are well in line with previous clinical/preclinical studies suggesting mitochondrial dysfunction and decreased energy production in uterine endometriosis tissue, 48 as proline catabolism in mitochondria serves as an important source of energy production and previous transcriptomics studies have demonstrated that there is reduced expression of proline oxidase (POX, a mitochondrial inner-membrane flavoenzyme involved in the catabolic degradation of the proline) due to overexpression of microRNA (known as MiR-23b). 31 , 49 Epigenetics studies on clinical samples have demonstrated that miRNA-23b exhibits regulatory roles, especially in the development of cancer, 50 , 51 and its overexpression is negatively correlated with the expression of tumor suppressor gene TUSC7 in endometrial carcinoma. 52 Studies have shown that miRNA-23b directly binds the POX mRNA 3′-untranslated region; thus, the overexpression of miRNA-23b is directly correlated with downregulation of mitochondrial proline oxidase (POX), as schematically depicted in ( Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%